Safety assessment of potentially inappropriate medications (PIM) use in older people and the factors associated with hospital admission - Varallo, Fabiana Rossi [UNESP]; Capucho, Helaine Carneiro; Planeta, Cleópatra Silva [UNESP]; Mastroianni, Patrícia de Carvalho [UNESP] (Frontiers, 2011)
Purpose: Potentially Inappropriate Medications (PIM) use in elderly people may be responsible for the development of Adverse Drug Reaction (ADR) which, when severe, leads to hospital admissions. Objectives: to estimate the prevalence of elderly who had used PIM before being admitted to hospital and to identify the risk factors and the hospitalizations related to ADR arising from PIM. Methods: A descriptive and cross-sectional study was performed in the internal medicine ward of a teaching hospital (Brazil), in 2008. With the aid of a validated form, patients aged ≥ 60 years, with length of hospital stay ≥ 24 hours, were interviewed about drugs taken prior to the hospital admission and the complaints/reasons for hospitalization. Results: 19.1% (59/308) of older patients had taken PIM before hospital admission and in 4.9%; there were a causal relation between the PIM taken and the complaint reported. PIM responsible for admissions were: amiodarone, amitriptyline, cimetidine, clonidine, diazepam, digoxin, estrogen, fluoxetine, lorazepam, short-acting nifedipine and propranolol. 47.0% of the clinical manifestations of PIM-related ADR were: dizziness, fatigue, digoxin toxicity and erythema. Only polypharmacy was detected as a risk factor for the occurrence of ADR of PIM (p = 0.02). Conclusion: PIM use in elderly people is not a risk factor for ADR-related hospital admission. Probably, severe ADR, which lead to hospitalizations of older people, can be explained by idiosyncratic response or the predisposition of these patients to develop adverse drug events, whether or not drugs are classed as PIM.